2006
DOI: 10.1089/ast.2006.6.490
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Tracing the Key Steps in the Origin of Life: The Aromatic World

Abstract: Life is generally believed to emerge on Earth, to be at least functionally similar to life as we know it today, and to be much simpler than modern life. Although minimal life is notoriously difficult to define, a molecular system can be considered alive if it turns resources into building blocks, replicates, and evolves. Primitive life may have consisted of a compartmentalized genetic system coupled with an energy-harvesting mechanism. How prebiotic building blocks self-assemble and transform themselves into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 207 publications
0
126
0
12
Order By: Relevance
“…PAHs are the most abundant polyatomic organic molecules in the universe, have been postulated to play important roles in the origin of life (16,17), and have been shown to stabilize short-chain fatty acid membranes (18). We therefore asked whether oxygenated derivatives of PAHs, such as 1-hydroxypyrene (while HPTS itself is also a hydroxypyrene derivative, it is unlikely to be prebiotically abundant), can be incorporated into vesicle membranes and act as photosensitizers that can absorb UV radiation, generate ROS, and facilitate the division of protocells.…”
Section: Resultsmentioning
confidence: 99%
“…PAHs are the most abundant polyatomic organic molecules in the universe, have been postulated to play important roles in the origin of life (16,17), and have been shown to stabilize short-chain fatty acid membranes (18). We therefore asked whether oxygenated derivatives of PAHs, such as 1-hydroxypyrene (while HPTS itself is also a hydroxypyrene derivative, it is unlikely to be prebiotically abundant), can be incorporated into vesicle membranes and act as photosensitizers that can absorb UV radiation, generate ROS, and facilitate the division of protocells.…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, the first communities of such physicochemical units were the gel-like membranous FeS bubbles produced at alkaline hydrothermal vents (66,98). Later, with the appearance of land, organic microspaces could have appeared, e.g., they could have emerged and evolved by drying and rewetting cycles from dissolved and suspended "cosmological oligomers" derived from hydrogen cyanide and from polyaromatic hydrocarbons (12,25,68), as further described in "Organic polymers and oligomers available on Hadean Earth" in the Appendix.…”
Section: The Necessity Of Microspacesmentioning
confidence: 99%
“…Despite this, their role in interstellar chemistry remains largely unexplored. It has been suggested that PAHs may be intimately involved in the molecular origin of life (Ehrenfreund et al 2006;Herd et al 2011) and that they may act as interstellar catalysts for the formation of molecular hydrogen (H 2 ; Habart et al 2004;Rauls & Hornekaer 2008), the most abundant molecule in space.…”
Section: Introductionmentioning
confidence: 99%